Explanatory Research: Work Ability, Work Discipline, and Employee Performance - Suwarto Suwarto; Desita Aliana (Jurnal Prajaiswara, 2020)
This study aims to determine a general overview of work ability, work discipline, and employee performance, in addition to knowing about the effect of workability and work discipline partially and simultaneously on employee performance—research using explanatory research with a quantitative approach and data collection through a questionnaire. The sample used by 35 employees remain at the Badan Kepegawian dan Pengembangan Sumber Daya Manusia Kabupaten Muaro Jambi. Data analysis is used in descriptive analysis and inferential analysis by observing the classical assumption test and multiple linear analysis. The results show that employability and discipline affect the performance of employees is 82,3%. At the same time, the remaining 17,7% of employee performance will be affected by variables such as wages, job security, working conditions, achievements, training, work experience, and others.